1 Zephaniah Swift, A Digest of the Laws of the State of Connecticut 552 (1822) - (:unkn) unknown (My University, 1822)
Chapter X, Trespass on the Case: Required guns to be made innoxious before transferring to an "incautious person."
Keywords: TRANSFER - DANGEROUS PERSONS